GLOBAL ADVERTISING MARKET – THE DYNAMICS OF THE LAST DECADE - Nichifor, Bogdan (Studies and Scientific Researches. Economics Edition, 2014)
Advertising as a form of impersonal communication aimed at a wide and diffuse audience, is the ideal tool to promote products targeting large markets in which consumers are not strong differentiated in terms motivations, preferences, attitudes, etc. Currently, in the global advertising market we can find extremely powerful organizations whose work often exceeds local and even regional economic sphere. From simple expertise in advertising, these organizations have expanded their services to a growing number of communication tools, organizing their activity to better respond to client’s requirements. These kind of advertising organizations alongside global advertisers are the key factors in the dynamics of this market. This article focuses on presenting some data regarding global expenditure in advertising, establishing as reference points the years 2002 and 2012. Moreover, we concentrated on expenditures by regions and advertisers, and on revenues obtained by advertising organizations and advertising networks, starting from official data provided by Advertising Age and Euromonitor.